Contrasting specific antibody response to BNT162b2 mRNA vaccination in SARS-CoV-2-naive and previously infected nursing home residents. Issue 3 (March 2022) - Chong, Yong; Tani, Naoki; Goto, Takeyuki; Yonekawa, Akiko; Ikematsu, Hideyuki; Shimono, Nobuyuki; Tanaka, Yosuke; Akashi, Koichi
Highlights: Antibody responses to SARS-CoV-2 vaccination were examined in nursing home residents. Anti-spike IgG levels after two doses were extremely lower in SARS-CoV-2-naive residents than in healthcare workers. Previously infected residents obtained rapid and robust antibody responses even after one dose. Increasing age did not result in reduced IgG levels in previously infected residents and healthcare workers. The pronounced responses in previously infected residents were observed even more than one year after infection.